2022
DOI: 10.21037/tlcr-22-137
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the perioperative outcomes between robotic-assisted thoracic surgery and video-assisted thoracic surgery in non-small cell lung cancer patients with different body mass index ranges

Abstract: Background: Non-small cell lung cancer (NSCLC) is the most common malignancy and one of the most common causes of cancer-related death worldwide. Robotic-assisted thoracic surgery (RATS) has gradually become a prevalent surgical method for patients with NSCLC. Previous studies have found that body mass index (BMI) is associated with postoperative outcomes. This study aimed to investigate the effectiveness of RATS compared to video-assisted thoracic surgery (VATS) in the treatment of NSCLC with different BMI, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Consequently, RATS surgery facilitates early extubation and discharge of patients, and this benefit is more pronounced after acquiring proficiency in RATS surgery (Period 2). This benefit stems from more meticulous anatomy and less pulmonary tissue damage of RATS surgery, which concurs with previous studies 16,19,26,40 …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consequently, RATS surgery facilitates early extubation and discharge of patients, and this benefit is more pronounced after acquiring proficiency in RATS surgery (Period 2). This benefit stems from more meticulous anatomy and less pulmonary tissue damage of RATS surgery, which concurs with previous studies 16,19,26,40 …”
Section: Discussionsupporting
confidence: 90%
“…Previous literature showed heterogeneity in comparing operative time between VATS and RATS surgeries. Most clinical studies did not report an advantage for RATS surgery in operative time, and some even reported a disadvantage of longer operative time, 17,19,23,28,31,32 which was also confirmed by a large‐scale multicenter prospective randomized controlled clinical trial 33 . This may be related to the extra trocar placement time required for Da Vinci surgery, more surgical incisions made by surgeons during RATS surgery, and more experience required by surgeons for RATS surgery 21,34 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…VATS has been widely used in NSCLC surgery, but VATS has some shortcomings. The application of RATS further solves the problems of long learning curve of VATS, counter-intuitive operation logic, lack of stereoscopic vision and poor instrument mobility [4,5]. At the same time, RATS can effectively reduce surgeon fatigue, and for procedures that require more delicate and complex operations with longer operating times, RATS helps the operator to focus and ensures a smoother procedure [6].…”
Section: Introductionmentioning
confidence: 99%